2004
DOI: 10.1097/01.asn.0000146689.88078.80
|View full text |Cite
|
Sign up to set email alerts
|

Src-Family Kinase Fyn Phosphorylates the Cytoplasmic Domain of Nephrin and Modulates Its Interaction with Podocin

Abstract: Abstract. Visceral glomerular epithelial cells (GEC) are critical for normal permselectivity of the kidney. Nephrin is a molecule that is expressed specifically in GEC in a structure called the slit diaphragm and is required for normal morphology and permselectivity of GEC. However, the mechanisms of action of nephrin are not understood precisely. The intracellular domain of nephrin has six conserved tyrosine residues. It was hypothesized that these tyrosine residues are phosphorylated by Srcfamily kinases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 29 publications
1
123
0
6
Order By: Relevance
“…Phosphotyrosines can also be critical intermediates in signal transduction pathways and mediate interactions with proteins containing SH2, WW, or phosphotyrosine-binding (PTB) domains. Tyrosine phosphorylation is a key modification in the SNS ortholog, nephrin (Li et al 2004;Jones et al 2006), and regulates signaling to two downstream pathways: one that activates Akt by phosphoinositide 3-kinase (PI3K) and another that directs actin rearrangements via Nck binding. Both the Akt signaling and Nck pathways are critical for nephrin function (Huber et al 2003a;Jones et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphotyrosines can also be critical intermediates in signal transduction pathways and mediate interactions with proteins containing SH2, WW, or phosphotyrosine-binding (PTB) domains. Tyrosine phosphorylation is a key modification in the SNS ortholog, nephrin (Li et al 2004;Jones et al 2006), and regulates signaling to two downstream pathways: one that activates Akt by phosphoinositide 3-kinase (PI3K) and another that directs actin rearrangements via Nck binding. Both the Akt signaling and Nck pathways are critical for nephrin function (Huber et al 2003a;Jones et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin was phosphorylated on Y1217 in nephrin WT/WT animals, whereas we could not detect any signal above background in nephrin Y3F/Y3F animals ( Figure 2C). Given that nephrin phosphorylation can affect nephrin-podocin interactions, 17,23 we performed dual-immunofluorescence staining for nephrin and podocin (Figure 2C) and found that both proteins were similarly expressed in a continuous pattern in the glomeruli of nephrin WT/WT and nephrin Y3F/Y3F animals. In accordance with this staining pattern, transmission electron microscopy (EM) revealed the presence of slit diaphragm structures in nephrin Y3F/Y3F animals ( Figure 2D).…”
Section: Generation Of Nephrinmentioning
confidence: 99%
“…Nephrin is tyrosine phosphorylated during glomerulogenesis and throughout life, 8,16,17 and decreases in nephrin phosphorylation on Y1217 are seen coincident with foot process effacement in human kidney diseases, including minimal change disease (MCD) 18 and membranous nephropathy. 19 Similarly, reduced phosphorylation of the downstream survival factor Akt on serine (S) 473 can be observed in MCD, 20,21 and inactivation of the actin binding protein cofilin is detected in patients with MCD, membranous nephropathy, and FSGS.…”
mentioning
confidence: 99%
“…La liaison de la néphrine à son ligand entraîne un regroupement des complexes dans des microdomaines lipidiques (lipid rafts). Cet événement va activer la protéine Fyn, un membre de la famille Src kinase, qui phosphoryle plusieurs résidus tyrosine situés à l'extré-mité carboxy-terminale de la néphrine ; à ce niveau, des protéines kinases et des protéines adaptatrices sont recrutées qui se lient ensuite à la néphrine via leurs domaines SH2 [7][8][9][10]. La phosphorylation de la néphrine par Fyn a deux conséquences essentielles ( Figure 3) : (1) elle active la PI3K via l'interaction du domaine SH2 de la sous-unité régulatrice p85 de cette dernière avec le domaine cytoplasmique de la néphrine tandis que la sous-unité catalytique p110 génère des phosphoinositides capables de recruter et d'activer la sérine thréonine kinase Akt, qui joue un rôle clé dans les processus de survie du podocyte.…”
unclassified
“…La phosphorylation de la néphrine par Fyn a deux conséquences essentielles ( Figure 3) : (1) elle active la PI3K via l'interaction du domaine SH2 de la sous-unité régulatrice p85 de cette dernière avec le domaine cytoplasmique de la néphrine tandis que la sous-unité catalytique p110 génère des phosphoinositides capables de recruter et d'activer la sérine thréonine kinase Akt, qui joue un rôle clé dans les processus de survie du podocyte. (2) Elle stabilise le complexe fonctionnel néphrine-podocine [10]. En effet, la déphos-peuvent être à l'origine d'une protéinu-rie massive quel que soit le mécanisme lésionnel initial.…”
unclassified